Narrowing of the Dorsal Vein Complex Technique during Laparoscopic Radical Prostatectomy: A Simple Trick to Simplify the Control of Venous Plexus - García-Segui, Alejandro; Sánchez, Manuel; Verges, Aleixandre; Caballero, Juan P.; Galán, Juan A. (Urology Journal, 2014)
Purpose: The control of the Dorsal Venous Complex (DVC) is crucial to the recovery of urinary continence during Laparoscopic Radical Prostatectomy (LRP). The size of DVC may affect the venous control. We developed a trick to simplify the suturing of the DVC. Materials and Methods: Forty-seven patients with localized prostate cancer were divided in two groups: group 1 (n = 24) underwent LRP with a conventional ligature of DVC, and in group 2 (n = 23) the venous control was done with “Narrowing” of DVC technique (N-DVC). Our technique involves maintaining pressure on a metallic urethral sound inserted into the urethra, just at the time of ligature. The width of DVC in group 2 was measured before and after applying the technique. The numbers of attempts to place the stitch adequately were recorded and compared in both groups. The demographic dates, perioperative dates and results were compared retrospectively. Results: Operative time, estimated blood loss, prostate weight, positive surgical margins rates and potency results showed no significant differences between the groups. The immediate 1-month, and 3-month continence rates were significantly greater in group 2 (30.4% vs. 12.5%, P = .048; 73.9% vs. 50%, P = .037, respectively). For all patients in group 2, width of DVC decreased and the ligation stitch was effective at the first attempt. In 37.5% of patients in group 1, the controlling of the DVC was obtained in more than one attempt.Conclusion: The N-DVC simplifies the control of DVC during LRP and may contribute to the early recovery of continence.